Three Close-Readings and Psychoanalysis on the Doctor in “The Use of Force” by William Carlos Williams - Zhang, Megan (Advances in Social Sciences Research Journal, 2024)
In this paper, I intend to present three primary interpretations of The Use of Force, a short story written by William Carlos Williams. Two of the three readings are explored in pre-existing analytical works of literature, and the third is my own reading to determine the resolve of the moral dilemma in the story. Throughout the paper, I will argue that autonomy is justified to be overridden at times, however it is still unjust. Structurally, the paper is organized in a way starting with definitions to establish a foundation that will aid in understanding the interpretations. Such definitions include concepts within the Hippocratic Oath and other terms related to society that still reign true with the concepts explored in The Use of Force. The understanding of such issues is vital to establishing a perspective towards the story, and brings out more space for discussions. Then, I will discuss and analyze the short story including analysis of the doctor’s behaviour, in-depth quote analysis, thought experiments, and finally interpretations relating to the real world.